The purification and identification of antioxidants and dipeptidyl peptidase IV inhibitory peptides from whey protein hydrolysates. Issue 3 (11th October 2022) - Yuanrong, Zheng; Jiakun, Pang; Zhenmin, Liu
Abstract: In the present study, whey protein was enzymatically hydrolyzed using an ultrahigh‐pressure synergistic enzymolysis method. The antioxidant activities and DPP‐IV inhibitory activities of the enzymatic hydrolysates were measured. Three‐layer isolation and purification were conducted on the enzymatic hydrolysates with antioxidant activity and DPP‐IV inhibitory activity by gel filtration chromatography and RP‐HPLC. The amino acid sequences were determined by LC‐MS/MS. The identified amino acid sequences were then synthesized, and their antioxidants and DPP‐IV inhibitory activities were determined. The results showed that 3 of the 14 polypeptides of N3‐8 exhibited high antioxidant activity. Among them, peptide DDQNPHSSN had both high antioxidant activity and DPP‐IV inhibitory activity. When the concentration was 1 mg/mL, then the ABTS radical scavenging rate, DPPH radical scavenging rate and reducing power were prominent, reaching 91.42%, 88.76%, and 0.637%, respectively, and DPP‐IV inhibitory activity reached 66.28%. Whey protease hydrolysates are expected to be commercially developed as functional peptides. Abstract : Whey protein was enzymatically hydrolyzed using an ultrahigh‐pressure synergistic enzymolysis method. The identified amino acid sequences were then synthesized, and their antioxidants and DPP‐IV inhibitory activities were determined. Whey protease hydrolysates could potentially be expected to be successfully commercially developed as functional peptides in the future.